Edible Film Made of Corn Starch-Carrageenan-Rice Bran: The Characteristic of Formula's Viscosity, Water Content, and Water Vapor Transmission Rate - Ratih Dwi Ismawanti; Widya Dwi Rukmi Putri; Erni Sofia Murtini; Heri Purwoto (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2020)
AbstractThis research aimed to obtain the best formulation of corn starch, carrageenan, and rice bran as the main components of edible film to improve formula’s viscosity, water content, and Water Vapour Transmission Rate (WVTR). This research was an experimental research using Randomized Complete Block Design (RCBD). The first factor was corn starch concentration (1.5%; 2.5%; 3.5%), the second factor was carrageenan concentration (0.67%; 1%; 1.33%), and the third factor was rice bran concentration (0.12%; 0.25%; 0.38%). The analysis of variance showed that the interaction of corn starch, carrageenan, and rice bran has a significant impact on the viscosity, water content, and WVTR value of the edible film. Based on the viscosity, water content, and WVTR value of the edible film, the best formulation was found in the edible film with the corn starch concentration of 2.5%, 1% carrageenan, and 0.25% rice bran. The formula's viscosity value of this edible film was 165.1 ± 5.3 cP, with 14.65 ± 0.05% of water content, and 60.13 ± 0.05 g/m2/h of WVTR value.Keywords: carrageenan, corn starch, edible film, rice bran Abstrak Tujuan dari penelitian ini adalah untuk mendapatkan formulasi terbaik dari pati maizena, karagenan, dan bekatul padi sebagai komponen dasar edible film untuk meningkatkan viskositas formula. kadar air, dan Water Vapour Transmission Rate (WVTR). Penelitian ini dilakukan secara eksperimental dengan menggunakan Rancangan Acak Kelompok (RAK). Faktor pertama adalah konsentrasi pati maizena (1,5% ; 2,5% ; 3,5%), faktor kedua adalah konsentrasi karagenan (0,67%; 1%; 1,33%), dan faktor ketiga adalah konsentrasi bekatul padi (0,12% ; 0,25% ; 0,38%). Hasil analisis ragam menunjukkan interaksi penambahan pati maizena, karagenan, dan bekatul padi berpengaruh nyata terhadap viskositas formula edible film, kadar air, dan nilai WVTR edible film. Formulasi terbaik sesuai karakteristik viskositas formula edible film, kadar air, dan nilai WVTR edible film adalah edible film dengan konsentrasi pati maizena 2,5%, karagenan 1%, dan bekatul 0,25% yang memiliki nilai viskositas formula edible film sebesar 165,1 ± 5,3 cP, kadar air edible film sebesar 14,65 ± 0,05%, dan nilai WVTR edible film sebesar 60,13 ± 0,05 g/m2/jam.Kata kunci: bekatul padi, edible film, karagenan, pati maizena